Inclusivity of Persons With Disabilities in the Work Sector During the Covid-19 Pandemic in Indonesia - Ayuningtyas, Dumilah; Ardi, Niken Sasanti; Barinda, Sandra; Larasanti, Ayudina; Napitupulu, Theresa; Margaretha, Cindy; Hasibuan, Sahfira Ulfa (Frontiers in Public Health, 2022)
Introduction The COVID-19 pandemic has had a significant impact on all levels of society, including people with disabilities, who in the pre-pandemic period faced obstacles in various sectors of life that affected efforts to fulfill basic living needs due to difficulties in accessing employment. Objective The objective of this study was to identify various factors and causal interaction patterns that affect the inclusiveness of workers with disabilities in pandemic situations, a dynamic system is needed to capture causal interaction patterns related to the inclusiveness of workers with disabilities in pandemic situations. Method This study used a causal loop diagram approach, which is part of a dynamic system that begins with determining the interaction of causal variables. The process of identifying and extracting data was carried out through a literature review and in-depth interviews with informants who met the principles of appropriateness and adequacy criteria. Result The interaction pattern between the factors that influence the inclusiveness of disabled workers was depicted in three causal loop diagrams covering three major domains, namely social, educational, and economic aspects. The three causal loop diagrams showed an increasingly dynamic interaction pattern during the COVID-19 pandemic, considering that workers with disabilities have greater vulnerability, which impacts their level of acceptance and inclusiveness at work. Recommendation There needs to be a specific policy to expand the acceptance of workers with disabilities by strengthening cross-sectoral collaboration and company commitments. The existence of a policy that prioritizes education, increases the budget, and procures adequate infrastructure for people with disabilities is a government commitment that is demanded to be fulfilled during the COVID-19 pandemic.